Morphology and Optical Investigations of InAs-QD/GaAs Heterostructures Obtained by Ion-Beam Sputtering - S. N. Chebotarev; A. S. Pashchenko; V. A. Irkha; M. L. Lunina (Journal of Nanotechnology)
A new ion-beam sputtering technique for obtaining self-assembled InAs quantum dots on GaAs (001) substrates is proposed. The current paper demonstrates that a temperature increase in a range from 450 to 550°C at ion current of 120 μA and energy of 150 eV leads to an expansion of average sizes of InAs hut-quantum dots. According to atomic force and electron microscopy, photoluminescence, and capacity-voltage measurements it was found that an increase of ion-beam current from 60 to 120 μA at a temperature of 500°C and energy of 150 eV slightly enlarges the average sizes of quantum dots from 15 nm to 18 nm while their dispersion is about 30%. At a current of 180 μA a surface density is 1.3·1011 cm−2, but under these conditions there is a very high dispersion of quantum dots up to 50%.